Legislaciones y políticas públicas de niñez y adolescencia en Costa Rica durante los años de 1989 a 2019 = Legislation and public policies for children and adolescents in Costa Rica during the years 1989 to 2019 - Barrantes Pereira, Rolando 1987-; Brenes Rodríguez, Milton Ariel 1989-; Sanabria Hernández, Marcela 1973- (2023)
En este artículo se presentan los resultados de un estudio de revisión bibliográfica y análisis que profundiza en la legislación y política pública de niñez y adolescencia en Costa Rica entre los años 1989 fecha de la Convención sobre los Derechos del Niñoy el 2019. Esta investigación se sitúa en el marco de acción del Observatorio Temático Interuniversitario de Derechos de la Niñezy la Adolescente (OBINA) y la subcomisión de Enlace y Política Pública; respondiendo así a sus objetivos definidos desde el plan estratégico y operativo. Para llevar a cabo este ejercicio investigativo se plantean tres fases: la identificación de leyes y políticas, la elaboración y definición de criterios para el análisis y el respectivo análisis por década, abarcando el período de 30 años aproximadamente. Los principales resultados, demuestran un interés del país por generar regulaciones y políticas para la promoción y defensa de los derechos de los niños, niñas y adolescente; pero también evidencian como aún hay una deuda en esta materia y falta de un posicionamiento aún mayor en el marco de la política pública, para que sea un tema trascendental y un eje transversal presente en todo el quehacer de política del país.
This article presents the results of a literature review and analysis study that delves into the legislation and public policy of children and adolescents in Costa Rica between the years 1989, the date of the Convention on the Rights of the Child, and 2019. This follow-up to the legislation on the rights of children and adolescents and its respective analysis based on specific criteria, seeks to build inputs, indicators, and references to develop subsequent recommendations from the Interuniversity ThematicObservatory for the rights of children and adolescents (OBINA) that can serve as inputs for decision-making in this matter and to generate a baseline for further research. This investigation is located within the framework of action of the OBINA and the Liaison and Public Policy sub-committee; thus, responding to its objectives defined from the strategic and operational plan of the Observatory. In order to carry out this research exercise, three phases are proposed that entail the identification of laws and policies, the elaboration and definition of criteria for analysis and the respective study by decade, covering the period of approximately 30 years. The main results show the country's interest in generating regulations and policies for the promotion and defense of children's and adolescents' rights. The results also demonstrate how there is still a debt in this matter and a lack of even greater positioning in the framework of public policy, so that it is a transcendental issue and a transversal axis present in all the country's political work.
En Revista estudios, Número 46 (junio-noviembre 2023)
Descripción basada en el contenido visto el 25 de marzo, 2025
También disponible en formato EPUB